Использование модели напряженно-деформированного состояния глаза для исследования структурной патологии экстраокулярных мышц - Кочина, М. Л.; Калиманов, В. Г. (ХНУРЕ, 2008)
The optical anisotropy of alive eye's cornea is caused by properties of corneal collagen, interposition of its fibres in a tissue of a cornea, level of intraocular pressure and a structurally functional condition of oculomotor muscles. The interferential picture in a form of rhombus which parameters depend on force of action and a place of attachment of oculomotor muscles is observed in polarized light on a cornea in a usual self. A method of calculation tensions in the eye was described. These tensions were provoked by mechanical influence of oculomotor muscles and intraocular pressure. The method is suitable for calculating tensions for eyes with different pathology oculomotor muscles.
Keywords: патология экстраокулярных мышц; состояние глаза